Towards the Interpretation of Medieval Latin-Czech Dictionary Equivalent Meanings - Nejedly, Petr (Bohemica Olomucensia, 2015)
The article deals with a way of reconstruction of several unique Old Czech lexical units from Klaret's Latin-Czech dictionaries. Both their form and meaning are uncertain and their Latin equivalents are hapax legomena, too. The reconstruction has to take into consideration some systemic features of the lexicon, grammatical (i.e. phonological, morphological, syntactic, and word-formative) rules and principles of the semantic development.
Keywords: Old Czech; Middle Latin; bilingual dictionaries; Klaret; lexical reconstruction; lexical meaning